MATHEMATICAL MODELLING WITH DELAYED DIFFERENTIAL EQUATIONS - Akbar Hanif, Evan
In this project, mathematical modeling is studied using differential equations as an example of the applications of mathematics so that students are motivated to study mathematics. The differential equations used in this project are ordinary differential equations and differential equations with time delays, which are discrete and continuous ones. In this project, the applications of differential equations are also studied in mathematical modeling related to exponential growth and decay, as well as logistic models.